2019
DOI: 10.1017/brimp.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

Changes over time in family members of adults with mild traumatic brain injury

Abstract: Objective:The impact of traumatic brain injury (TBI) extends beyond the person who was injured. Family caregivers of adults with moderate to severe TBI frequently report increased burden, stress and depression. Few studies have examined the well-being of family members in the mild TBI population despite the latter representing up to 95% of all TBIs.Methods:Five areas of well-being were examined in 99 family members (including parents, partners, siblings, other relatives, adult children, friends or neighbours) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…It is possible that the family members’ mental health may have been less affected because they did not have the same caregiver responsibilities or role changes as those of patients with more severe injuries as reported in the PariS-TBI study (47.7 points vs. 36.7 points) [ 50 ]. A study on caregivers of persons with mild TBI demonstrated that, at 6 months after the injury, the HRQL reached levels similar to the general population, suggesting that mild TBI has less impact on the family members’ mental health compared with more severe injuries [ 51 ]. We included family members 6–18 months post-injury supporting this finding on overall mental health; however, this impression was not clear-cut.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the family members’ mental health may have been less affected because they did not have the same caregiver responsibilities or role changes as those of patients with more severe injuries as reported in the PariS-TBI study (47.7 points vs. 36.7 points) [ 50 ]. A study on caregivers of persons with mild TBI demonstrated that, at 6 months after the injury, the HRQL reached levels similar to the general population, suggesting that mild TBI has less impact on the family members’ mental health compared with more severe injuries [ 51 ]. We included family members 6–18 months post-injury supporting this finding on overall mental health; however, this impression was not clear-cut.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of those with mTBI have found that social support predicts lower symptom reporting (Quan Zeng et al, 2016; Temple et al, 2016) and increased satisfaction with life (Seidl et al, 2015). However, mTBI can negatively impact family functioning, causing disruption to relationships with the person with mTBI (Jones et al, 2020; Nelson et al, 2019; Orff et al, 2016; Pugh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a major cause of death and disability worldwide (Hyder, Wunderlich, Puvanachandra, Gururaj, & Kobusingye, 2007). The experience of TBI can be devastating for patients, families and the wider community (Holloway et al, 2019;Jones et al, 2020). The injured person may face months of physical rehabilitation (Hellweg & Johannes, 2008); they may have new accommodation and employment needs (Huebner et al, 2003); and they may confront the fundamental challenge of the reconstruction of their personhood (Gracey et al, 2008;Levack et al, 2010).…”
Section: Introductionmentioning
confidence: 99%